Student Smoking, School Discipline, and the Second Principle of Pancasila: A Qualitative Case Study of Violence in a Senior High School in Banten, Indonesia - arie_febrianto febrianto; Didik Nugroho; Sri Harjanto; Sri Tomo (International Journal of Law and Legal Ethics, 2026)
https://docs.google.com/document/d/1s3YssutAKvvZruahXtOLJwLsR-VtHx56/edit?usp=sharing&ouid=112411647335528457171&rtpof=true&sd=true